Hepatitis C seropositivity is not a risk factor for sensory neuropathy among patients with HIV - Cherry, C.; Affandi, J.; Brew, B.; Creighton, J.; Djauzi, S.; Hooker, D.; Imran, D.; Kamarulzaman, A.; Kamerman, P.; McArthur, J.; Moore, R.; Price, Patricia; et al. (Lippincott Williams & Wilkins, 2010)
BACKGROUND: Sensory neuropathy (SN) is common in patients with HIV. Hepatitis C (HCV) coinfection is often cited as an HIV-SN risk factor, but data to support this are lacking. This collaboration aimed to examine the association between HCV serostatus and SN risk among ambulatory HIV-positive patients. METHODS: Patients with HIV were assessed in cross-sectional studies in Baltimore, Jakarta, Johannesburg, Kuala Lumpur, Melbourne, and Sydney for SN (defined by both supportive symptoms and signs). HCV seropositivity was assessed as an SN risk using a ? test, followed by logistic regression modeling to correct for treatment exposures and demographics. RESULTS: A total of 837 patients of African, Asian, and Caucasian descent were studied. HCV seroprevalence varied by site (Baltimore n = 104, 61% HCV+; Jakarta 96, 51%; Johannesburg 300, 1%; Kuala Lumpur 97, 10%; Melbourne 206, 16%; Sydney 34, 18%). HCV seropositivity was not associated with increased SN risk at any site, but was associated with reduced SN risk in Melbourne (p = 0.003). On multivariate analyses, the independent associations with SN were increasing age, height, and stavudine exposure. HCV seropositivity was not independently associated with an increased SN risk at any site, but associated independently with reduced SN risk in Baltimore (p = 0.04) and Melbourne (p = 0.06). CONCLUSIONS: Hepatitis C (HCV) seropositivity was not associated with increased sensory neuropathy risk among HIV-positive patients at any site. While we were unable to assess HCV RNA or liver damage, the data suggest that HCV coinfection is not a major contributor to HIV-SN. GLOSSARY: HCV = hepatitis C; SN = sensory neuropathy. Copyright © 2010 by AAN Enterprises, Inc.